Perancangan Museum Adat Banten Dengan Arsitektur Vernakuler Di Pasar Lama Kota Tangerang - Indah Meyla Puspitasari; Karya Subagya; Anggraeni Dyah Sulistiowati (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2023)
The Pasar Lama area in Tangerang City has a role as an area with historical and cultural values. Old buildings in the Pasar Lama are used as historical tourist objects, witnessing the development of the city of Tangerang. The City of Tangerang launched a program to build an educational tourism area to restore its former glory and increase tourism potential. In the zoning regulations that support tourism and cultural zones in the Pasar Lama area which are now occupied by buildings that do not comply with the zoning regulations. The development of the museum as an educational tourism area was also appointed as an effort to preserve historical and cultural objects, with an emphasis on regional-level museums that are able to cover a wider area and exhibit a richer collection. This museum is seen as the right choice to raise the tourism potential in Tangerang with the theme of Banten's Indigenous culture.